DEVELOPMENT OF MULTI WALLED CARBON NANOTUBES GAS SENSOR BASED ON IONIZATION - MOHAMED SAHEED, MOHAMED SHUAIB (2014)
Multiwalled carbon nanotubes (MWCNT) have started to be developed as the sensing element for the ionization-based gas sensors due to the demand for improved sensitivity, selectivity. stability and other sensing properties beyond what can be ot1ered by the conventional ones. Although these limitations have been overcome. the problems still remain with the conventional ionization-based gas sensors in that they are bulky and have large breakdown voltage and high temperature such that they are not safe for operation. Nanostructured electrode in the form of aligned MWCNT array with uniform nanotips can enhance the electric field significantly even at a low applied voltage. The objective is to develop novel gas sensor with enhanced sensing properties by growing specific MWCNT and integrating this sensing element in an ionization contiguration. Aligned MWCNT arrays were grown in thermal and floating catalyst chemical vapor deposition (CVD) system.